2020
DOI: 10.1016/j.bulcan.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation de l’application des recommandations des cancers de l’endomètre de type 2 : étude rétrospective multicentrique

Abstract: Introduction Les carcinomes de l’endomètre de type 2 sont des cancers peu fréquents et de mauvais pronostique. Il existe très peu d’étude analysant leur prise en charge. L’objectif de l’étude était d’étudier la prise en charge des carcinomes de type 2 dans nos centres en évaluant l’application des recommandations. Matériel et méthode Il s’agit d’une étude multicentrique rétrospective enregistrant les cancers de l’endomètre de type 2 pris en charge de janvier 2009 à déce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…More than half of the patients (53.4%) were diagnosed with stage I of the disease. This result is consistent with those of Chekman et al [10] and Scattarelli et al [12], who reported 62.7% and 46% of patients with stage I endometrial cancer, respectively. Endometrioid adenocarcinoma was the most frequent histological type in our study (68.6%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…More than half of the patients (53.4%) were diagnosed with stage I of the disease. This result is consistent with those of Chekman et al [10] and Scattarelli et al [12], who reported 62.7% and 46% of patients with stage I endometrial cancer, respectively. Endometrioid adenocarcinoma was the most frequent histological type in our study (68.6%).…”
Section: Discussionsupporting
confidence: 93%
“…Most of the patients were postmenopausal (91.9%). This result confirms that endometrial cancer is mainly a pathology of postmenopausal women [11] [12]. The same observation was made by Ouédraogo et al [6], who found a proportion of 89.5% of postmenopausal patients in their study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Subtype 1 (endometrioid endometrial carcinoma) accounts for approximately 80% of endometrial cancers; it is easily diagnosable in early stages and has a good prognosis. Subtype 2 (non-endometrioid endometrial carcinoma) accounts for approximately 20% of endometrial carcinomas, is highly invasive, and has a poor prognosis (5). Most patients with endometrial carcinoma are diagnosed at an early stage of the disease, and the 5-year survival rate is relatively high (65.27%-81.2%) (6,7).…”
Section: Introductionmentioning
confidence: 99%